Gridded ELAC SB3050 multibeam-echosounder bathymetry of cruise POS499 - Wintersteller, Paul (MARUM - Center for Marine Environmental Sciences, University Bremen, 2018)
Bathymetry based on data recorded during POS499 between 04.05.2016 and 22.05.2016 in Mediterranean Sea. The aim of POS499 was to investigate several mud volcanoes from 4 regional areas of the Calabrian Arc with the MARUM AUV SEAL. CI Citation: Paul Wintersteller (seafloor-imaging@marum.de) as responsible party for bathymetry post-processing and its products. Detailed description of the data source: During the RV POSEIDON cruise POS499 the ELAC SB3050 multibeam echo sounder with a nominal sounding frequency of 50 kHz was utilized. 384 beams are formed for each ping while the seafloor is detected using amplitude and phase information for each beam sounding. For further information consult http://www.mdsys.co.kr/down/ELAC/SB_3050.pdf. During the POS499 cruise the swath - width has been set to AUTO mode and was commonly observed at around 80°. This given swath ‐ width refers to a coverage of about 1.6 times the water ‐depth and reduces the max. number of beams collected per ping to less than 240. Most of the time the multi‐ping mode has been used with a receiver reception gain value of 45dB. The recorded bathymetry covers in total 880 km and the mapped area is based on the bathymetry results from the M111 & M112 cruises. Responsible person for hydroacoustics during this cruise / PI: Paul Wintersteller (pwintersteller@marum.de) Description of data processing: Postprocessing and products were conducted by the Seafloor-Imaging & Mapping group of MARUM/FB5, responsible person: Paul Wintersteller (seafloor-imaging@marum.de). The open source software MB-system suite (Caress, D.W., and D.N. Chayes, MB-System Version 5, Open source software distributed from the MBARI and L-DEO web sites, 2000-2012.) was utilized for this purpose. A tide correction was applied, based on the Oregon State University (OSU) tidal prediction software (OTPS) that is retrievable through MB-System. Tidal changes in the Mediterranean Sea are up to max. 1m. CTD measurements were taken during the POS499 cruise, and these were sufficient to represent the changes in the sound velocity throughout the study area. Further pitch and heave corrections were not applied for the POS499 data though a roll off-set of -0.46° was applied (mbset). Bathymetric data has been manually cleaned for existing artefacts with mbeditviz. NetCDF (GMT) grids of the product and the statistics were created using mbgrid. No total propagated uncertainty (TPU) has been calculated to gather vertical or horizontal accuracy. The currently published bathymetric grid of the cruise has a resolution of 70 m. A higher resolution is, at least partly, achievable. The grid extended with _num represents a raster dataset with the statistical number of beams/depths taken into account to create the depth of the cell. The extended _sd -grid contains the standard deviation for each cell. All grids produced are retrievable through the PANGAEA database (www.pangaea.de). Chief Scientist: Gerhard Bohrmann (gbohrmann@marum.de) CR: https://elib.suub.uni-bremen.de/peid=P00105556 CSR: https://www2.bsh.de/aktdat/dod/fahrtergebnis/2016/20160083.htm